Evidence for the Possible Biological Significance of the igf-1 Gene Alternative Splicing in Prostate Cancer - Philippou, Anastassios; Armakolas, Athanasios; koutsilieris, Michael (Frontiers in Endocrinology, 2013)
Insulin-like growth factor I (IGF-I) has been implicated in the pathogenesis of prostate cancer (PCa), since it plays a key role in cell proliferation, differentiation and apoptosis. The IGF-I actions are mediated mainly via its binding to the type I IGF receptor (IGF-IR), however IGF-I signaling via insulin receptor (IR) and hybrid IGF-I/IR is also evident. Different IGF-I mRNA splice variants, namely IGF-IEa, IGF-IEb and IGF-IEc, are expressed in human cells and tissues. These transcripts encode several IGF-I precursor proteins which contain the same bioactive product (mature IGF-I), however, they differ by the length of their signal peptides on the amino-terminal end and the structure of the extension peptides (E-peptides) on the carboxy-terminal end. There is an increasing interest in the possible different role of the IGF-I transcripts and their respective non-(mature)IGF-I products in the regulation of distinct biological activities. Moreover, there is strong evidence of a differential expression profile of the IGF-I splice variants in normal vs. PCa tissues and PCa cells, implying that the expression pattern of the various IGF-I transcripts and their respective protein products may possess different functions in cancer biology. Herein, the evidence that the IGF-IEc transcript regulates PCa growth via Ec-peptide specific and IGF-IR/IR-independent signaling is discussed.